Pelatihan dan Kompetensi terhadap Kinerja Pegawai TPI Imigrasi II Parepare - Syach, M. Alfian; Nur, Irawati; Anggerwati, A. Indah; Rifani, Riza Amalia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine the effect of training and competence on employee performance at the Immigration Checkpoint in Immigration Office II Parepare. The analysis methods used include validity tests, reliability tests, multiple linear regression, partial tests, simultaneous tests, and the coefficient of determination to tests the hypotheses. The results of the study show that training partially affects employee performance, where as competence simultaneously affect employee performance. The R Square value obtained is 17,5%, indicating that the influence of training and competence on employee performance is 17,5%, while the remaining 82,5% is influenced by other variables not examined in this study.